Comparison of Mathematics Learning Outcomes Online and Offline Students at Senior STIKES Medan Using Independent T-Test - Dame Meldaria Sipahutar (research, training and philanthropy institution Natural Aceh, 2023)
Mathematics is one of the compulsory subjects in formal education and has an essential role in the world of education. This research was conducted to determine the results of learning mathematics in students at STIKes Senior Medan online and offline. This study used a quasi-experiment using the comparative method. The number of samples used was from two classes and given two other learning treatments, namely online and offline. The samples used were 34 students for the odd school year 2020/2021 (online) and 39 for the bizarre school year 2021/2022 (offline). Then a normality and homogeneity test was carried out using the Statistical Product and Service Solution (SPSS) application program to determine whether the data were normally distributed and had the same variance. The results of testing the hypothesis using the independent t-test sig (2-tailed) 0.048 <0.05, so that as a basis for decision making in the independent sample t-test, it can be concluded that Ho is rejected and Ha is accepted. Thus, with a 95% confidence level, there is a significant (significant) difference between online learning UAS mathematics learning outcomes and offline learning UAS mathematics learning outcomes.